Encouraging Pupils to Work Together - Stepišnik , Katarina (Širjenje obzorij o poučevanju glasbe, 2025)
Collaboration in the classroom is a fundamental approach to enhancing academic achievement, social skills, and interpersonal relationships among students. This section explores effective techniques for fostering collaboration, including the development of group dynamics, the implementation of group projects, conflict resolution strategies, the promotion of mutual respect, and methods for assessing both individual and group contributions. The discussion is grounded in key research emphasizing the importance of cooperative learning in the educational process.